(NoSNOWY ISSLEDOWATELXSKOJ DEQTELXNOSTI PEDAGOGA(B-(NMUZYKANTA(B.s (NU^EBNOE POSOBIEs - (N|(B.(Nb(B.(NaBDULLINs ((NmOSKWAs (NpLANETA mUZYKIs, 2014)
(Nw U^EBNOM POSOBII ANALIZIRUETSQ SU]NOSTX OSOBENNOSTI(B, (NWIDY U^EBNO(B-(NISSLEDOWATELXSKOJ DEQTELXNOSTI PEDAGOGA(B-(NMUZYKANTA(B.s
Keywords: (NmETODIKAs